Biosimilars: Company Strategies to Capture Value from the Biologics Market - Juan Leonardo Martínez-Hurtado; Bruno Calo-Fernández (MDPI AG, 2012)
Patents for several biologic blockbusters will expire in the next few years. The arrival of biosimilars, the biologic equivalent of chemical generics, will have an impact on the current biopharmaceuticals market. Five core capabilities have been identified as paramount for those companies aiming to enter the biosimilars market: research and development, manufacturing, supporting activities, marketing, and lobbying. Understanding the importance of each of these capabilities will be key to maximising the value generated from the biologics patent cliff.